Hubungan Kepatuhan Penggunaan Obat Antihipertensi dengan Kualitas Hidup Pasien Hipertensi - Wagiu, Ariel E.; Wiyono, Weny I.; Mpila, Deby A. (e-CliniC, 2025)
Abstract: Hypertension is a condition where systolic and diastolic blood pressure exceeds values of 140 mmHg and 90 mmHg, respectively. Patient compliance related to the use of antihypertensive drugs is a major factor in improving the quality of life of hypertensive patients. This study aimed to determine the relationship between the level of compliance in consumption of antihypertensive drugs and the quality of life of hypertensive patients at Puskesmas Kawangkoan (public health center). This was an observational and analytical study with a cross-sectional approach. A total of 80 patients as samples were obtained using purposive sampling technique. Data on the level of compliance with drug use were obtained from the Morisky Medication Adherence Scale (MMAS-8) questionnaire and the Short-Form 36 (SF 36) questionnaire to measure quality of life in hypertensive patients. The results obtained 80 patients as samples. Data were statistically analyzed using the Spearman-rho test which showed a significant relationship between the level of compliance in drug consumption and the quality of life of hypertensive patients at Puskesmas Kawangkoan (p=0.000<0.05). In conclusion, there is a significant relationship between the level of compliance in antihypertensive drug consumption and the quality of life of hypertensive patients at Puskesmas Kawangkoan. Keywords: hypertension; medication adherence; quality of life.   Abstrak: Hipertensi adalah keadaan dimana tekanan darah sistolik dan diastolik melebihi nilai  140 mmHg dan 90 mmHg. Kepatuhan pasien dalam penggunaan obat antihipertensi merupakan faktor utama dalam peningkatan kualitas hidup pasien. Penelitian ini bertujuan untuk mengetahui hubungan tingkat kepatuhan penggunaan obat antihipertensi dengan kualitas hidup pasien hipertensi di Puskesmas Kawangkoan. Jenis penelitian ialah analitik observasional dengan desain potong lintang. Sampel penelitian diperoleh dengan teknik purposive sampling. Data tingkat kepatuhan penggunaan obat diperoleh dari kuesioner Morisky Medication Adherence Scale (MMAS-8) dan kuesioner Short-Form 36 (SF 36) untuk mengukur kualitas hidup pada pasien hipertensi. Hasil penelitian mendapatkan sebanyak 80 pasien sebagai sampel. Hasil uji Spearman-rho menunjukkan adanya hubungan bermakna antara tingkat kepatuhan penggunaan obat dengan kualitas hidup pasien hipertensi (p=0,000<0,05). Simpulan penelitian ini ialah terdapat hubungan bermakna antara tingkat kepatuhan penggunaan obat antihipertensi dengan kualitas hidup pasien hipertensi di Puskesmas Kawangkoan. Kata kunci: hipertensi; kepatuhan penggunaan obat; kualitas hidup